2016
DOI: 10.1007/s10549-016-4062-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the mutational landscape of triple-negative breast cancer in African Americans and Caucasians

Abstract: Background Triple negative breast cancer (TNBC) occurs at higher frequency in African Americans compared with Caucasians. It is unclear if the biology of TNBC is different in African American versus Caucasians. In this study, we sought to evaluate racial differences in the molecular pathology of TNBC. Methods Using data from The Cancer Genome Atlas, we identified TNBC patients with information on race. We analyzed differences in clinical characteristics, tumor somatic mutations, and gene expression patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 34 publications
9
52
0
Order By: Relevance
“…These pan-cancer findings are consistent with previous results from studies based on a single cancer type. For example, recent studies on breast cancer from the TCGA cohort (Ademuyiwa et al, 2017; Huo et al, 2017; Keenan et al, 2015) demonstrated that AAs had more TP53 mutations and fewer PIK3CA mutations. These observations not only further our understanding of the contributions of genetic ancestry to cancer disparities, but may also inform personalized treatment of cancer patients from racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pan-cancer findings are consistent with previous results from studies based on a single cancer type. For example, recent studies on breast cancer from the TCGA cohort (Ademuyiwa et al, 2017; Huo et al, 2017; Keenan et al, 2015) demonstrated that AAs had more TP53 mutations and fewer PIK3CA mutations. These observations not only further our understanding of the contributions of genetic ancestry to cancer disparities, but may also inform personalized treatment of cancer patients from racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…This shared genetic background may confer similarities in cancer incidence and outcomes in populations. Recent large-scale genomic profile studies in individual cancer types, such as prostate (Huang et al, 2017; Petrovics et al, 2015; Powell et al, 2013; Wang et al, 2017), breast (Ademuyiwa et al, 2017; Huo et al, 2017; Keenan et al, 2015; Loo et al, 2011), colon (Guda et al, 2015), lung (Araujo et al, 2015; Campbell et al, 2017; Kytola et al, 2017), gastric (Schumacher et al, 2017), esophageal (Deng et al, 2017), and kidney (Krishnan et al, 2016) cancers have robustly demonstrated that genomic differences in cancers exist among distinct racial and ethnic populations. Consistently, it has been reported that the genetic background of patients may influence specific somatic alterations in cancer genomes during tumorigenesis (Carter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being a biological entity, TNBC is a heterogeneous disease, and subtyping is necessary to establish molecular-based therapies [7]. Different subgroups of TNBC have been identified on the basis of protein expression, mRNA signatures, and genomic alterations, either on the somatic and/or the germline level [6,8,9]. Clinical trials of targeted therapies (e.g., immune checkpoint inhibitors, androgen receptor inhibitors, poly(ADP-ribose)polymerase (PARP) inhibitors, vascular endothelial growth factor receptor inhibitors) and platinum-based therapies in TNBC are ongoing, which have recently been reviewed in detail [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, other observations suggest a role for molecular differences in cancer survival disparities. 11 Whereas some studies have explored somatic alterations in individual cancers, [12][13][14] little is known about how the macroenvironment affects the epigenetic landscape among the different races. 9 A comparison of TNBC in AA versus EA patients has demonstrated a gene expression signature consistent with increased loss of BRCA1 expression, increased activation of insulin-like growth factor 1 receptor, and increased expression of vascular endothelial growth factor-activated genes in AA patients.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, AA patients with breast, head and neck, or endometrial cancer have higher levels of chromosomal instability and frequency of TP53 mutations and CCNE1 amplification than white patients. 11 Whereas some studies have explored somatic alterations in individual cancers, [12][13][14] little is known about how the macroenvironment affects the epigenetic landscape among the different races. 15,16 Epigenetic differences are particularly relevant because they can be shaped by environmental factors, such as chronic stress, social interactions, and toxins.…”
Section: Introductionmentioning
confidence: 99%